Talaqqi and Takrir Methods in Improving the Quality of Reading & Memorizing the Qur'an - Ilham Tumanggor; Hasbi Ramadani; Candra Gunawan (As-sunnah: Jurnal Pengabdian Masyarakat, 2022)
The community of Masjid Nurul Falah Balai Talang has established Madrasah Diniyah Al-Qur'an (MDA) as a forum for children to learn the Qur'an. Based on the conditions observed that the process of learning the Qur'an in this place is not conducive, the cause is the lack of teachers and not comparable to the children who want to learn the Qur'an in Madrasas. To improve and develop their ability to read and memorize the Qur'an, it is necessary to carry out community service activities. The program's research method used in community service activities is Asset Based Community Development (ABCD). Several stages were carried out to implement ABCD including the inculturation stage, the design stage, the define stage, and the reflection stage. After community service activities were carried out, the quality and quantity of memorization of the Qur'an increased, and the public's interest increased to study the Qur'an. The result of the activity is that the community at MDA Nurul Falah Balai Talang uses the talaqqi and takrir methods in learning the Qur'an to improve skills in reading and memorizing the Qur'an students. During the twenty-three days of the application of the method, there was a significant increase especially in the memorization and reading of the students, so the community was satisfied with the results that had been achieved during the twenty-three days. So it is known that this method is effective in tahfidz and tahsin activities.